STRATEGI UNTUK MENINGKATKAN DAN MENGEMBANGKAN MINAT MENGUNJUNGI TURIS OBYEK WISATA DANAU SUMATERA BARAT - Emil Salim; Winda Afriyenis (JOURNAL OF APPLIED BUSINESS ADMINISTRATION, 2020)
This research aims to formulate a strategy in an effort to increase and develop interest in tourist visits to the Twin Lake tourist attraction in West Sumatra. The uniqueness and renewal in this research is located in the object of study combined with using a qualitative approach and strategy formulation analysis tools namely SWOT analysis and QSPM (Quantitative Strategic Planning Matrix) to analyze internal and external factors and what strategies should be applied to improve and develop objects Twin Lake tourism in West Sumatra. The findings of this study found a number of evaluations and strategic recommendations, including the attractions of the Twin Lakes in West Sumatra have a very unique and special natural beauty that is rarely owned by other attractions. However, weak capital and local government support and the absence of foreign investors make the Twin Lakes Lake attractions in West Sumatra currently still in the criteria less desirable by tourists. West Sumatra Twin Lake tourism object is expected to be able to find investors - investors in efforts to improve and develop West Sumatra Twin Lake tourist attraction.